The Effect of Non-Executive Directors and Institutional Ownership on Firm Size: The Role of Audit Committee as a Moderating Variable - Hidayah, Retnoningrum; Ratmono, Dwi (Accounting Analysis Journal, 2025)
Purpose: The study explores the influence of non-executive directors (NED) and institutional ownership on firm size. Additionally, it examines the role of the audit committee as a moderating variable. Method: The research uses data from the annual reports on the Indonesia Stock Exchange (IDX). The research focuses on the banking industry from 2019 to 2023 with 105 units of analysis. The study employs moderated regression analysis (MRA) to assess the relationship among the variables. Findings: The results indicate that non-executive directors and institutional ownership have a negative effect on firm size. In addition, the audit committee significantly contributes to moderating the relationship between non-executive directors (NED), institutional ownership, and firm size. This study contributes to companies where the audit committee can mitigate the adverse effects of corporate governance and reinforce governance structures to promote firm growth. Novelty: As far as the researcher’s knowledge, this is the first research that examines the role of the audit committee as a moderating variable on the framework of the relationship between non-executive directors, institutional ownership, and firm size.